Management of Oral Feeding Challenges in Neonatal Intensive Care Units (NICUs): A National Survey in China - Lyu, Tianchan; Zhang, Yuxia; Hu, Xiaojing; Gu, Ying; Li, Liling; Lau, Chantal (Frontiers in Pediatrics, 2020)
Abstract Objectives: To investigate the current practices of oral feeding difficulties facing high-risk infants in Chinese NICUs. Methods: A questionnaire to survey infant oral feeding practices was distributed to 100 level II and III Chinese neonatal intensive care units (NICUs). Results: Responses were obtained from 88 NICUs. No Units had any structured guidelines regarding the management of infant oral feeding as they transitioned from tube to independent oral feeding. In 54 (61.4%) NICUs, nurses and physicians made shared decisions on when oral feeding were to be initiated. Fifty-four (61.4%) and 22 (25.0%) NICUs used postmenstrual age (PMA) or weight at PMA as a criterion for initiating oral feedings, respectively. The top three criteria to determine introduction of oral feeding were severity of disease, presence of sucking reflex, and trial feeding success. Adverse events were used by 78 Units as indices of oral feeding difficulty. Twenty (22.7%) and 25 (28.4%) Units had access to occupational therapists or nurses who provided oral motor interventions during feeding, i.e., oral support (chin and cheek support, aid to deglutition), nonnutritive sucking with pacifier, and oral stimulation. Conclusions: The management of oral feeding issues in NICUs vary widely in China in relation to the assessment of readiness to oral feeding, daily oral feeding practices and interventions used by staff. It is proposed that an educational program focused on the physiology of infant oral feeding, available evidence-based tools and interventions would assist NICU caregivers develop structured guidelines to improve infants’ safe and efficient attainment of independent oral feeding.